Educação de surdos: um estudo sobre as implicações da utilização de mediadores tecnológicos na formação de professores - (:unkn) unknown (Universidade Federal do Amazonas, 2010)
The theme of this study is the education of the deaf and the implications of the use of technological intermediaries in teacher`s education. Aiming at large, understand how to configure and articulate New Technologies of Information and Communication in Deaf Education in the city of Manaus-AM. The specific objectives are to identify the contributions of New Information Technologies and Communications for the Education of Deaf and see how the new technologies of information and communication are negotiated and problematized by the deaf and professionals involved with the education of this group. The research was performed at the Course of Literature / Brazilian Sign Language, developed in distance mode from the Federal University of Santa Catarina, in the center of the Federal University of Amazonas. The methodological procedures were graded in qualitative methodology and used the technique of individual interviews with semi-structured instruments. The research subjects were the deaf students and technical-pedagogical staff of the pole of the Federal University of Amazonas. Among the results, we identified that the use of technological mediators contributes, positively, to the training of deaf educators, especially if they are planned according to their specificities, namely, from the sign language and visual culture. It s considered of utmost importance that institutions of higher education in the country, especially public ones, should offer quality education and personalize service to deaf people, because these actions constitute themselves in affirmative and citizen policies and contribute to reducing social exclusion and education of these people.
Keywords: Educação de Surdos; Mediadores Tecnológicos; Língua de Sinais; Education of the Deaf; Technological Mediators; Sign Language; CIÊNCIAS HUMANAS: EDUCAÇÃO